UTILIZACIÓN DE ALMIDÓN DE PAPA (SOLANUM TUBE), SAPONINA DE QUINUA (CHENOPODIUM QUINOA) Y ACEITE ESENCIAL DE ORÉGANO (ORIGANUM VULGARE) EN LA ELABORACIÓN DE UN RECUBRIMIENTO BIOACTIVO - ZAMBRANO VERDEZOTO, JENIFFER CARLINA (2025)
The edible coatings and films used in industries today are made with chemical ingredients and these are harmful to people's health, leading them to suffer from chronic diseases